(untitled) (Journal Of Educational and Psychological Researches, 2015)
The research aim to know the effect of note–taking by computer method as amentalactivators in achievement of physics subject for the first intermediate class students. To investigate from aim of the research the research sample was chosen from the first intermediate class students in Al–mutamyzat secondary school for girls. Which belongs to the general administration for the second karkh education which randomly chosen from (9) schools for distinct female students in Baghdad. Then randomly chosen two sections form three about (80) female students at (66.667%) from total sample it’s about (120) female student in the three sections. The randomly chosen too, section (a) to represent experimental group it’s about (41) female students at (34.167%) and the section (g) represent the control group it’s about (39) female students at (32.5%) from the research society then the experimental and control groups design with apost–test was chosen the two groups have been equalization in the two variables that is (the female students g achievement in physics and mathematics subjects for mid year) and in another variable swhich effect on rocedure of the research. Then the experimental group female students was teaching by using note–taking by computer method as mentalactivators but the control female students was teaching by traditional method for physics subject before that the researcher put the special aim sand the behavior objectives in the light of bloom classification and she makes the teaching plane swhich was exposing them of specialists in physics and its teaching methods to ascertain from their validity for application. Then the esearcher prepared an achievement post-test which kind multiple–hoice with three chosen depend on the physics subjects include (38) items in the light of bloom classification by remember, understanding, and application level. It’s by using half–spilt method and the persone quation the reliability was (0.75) and correct that by using spearman–brown equation (r21) it was (0.85) the experiment was conducted in these condterm of the academic year (2012–2013). The data were statistically processed by using t-test formula for two Unequal independent samples then the stand by hypothesis was accepted that’s there is statistic significant difference at (0.05) level between two averages for the female students which studied by using note–taking by computer method and for the female student which studied by using the traditional method in achievement for physics subject for the first intermediate class. Then in the light of the research results the researcher commended the education mainstay and higher teaching mainstay to adoption for the note–taking by computer method to training the physics teacher to use it in their teaching and include it in the decision of the curriculum and the researcher suggested to makes imilar studies in several subjects and the stages of study to know it effect in achievement end another variables.